2011
DOI: 10.3382/ps.2010-00973
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional equivalency evaluation of transgenic maize grain from event DP-Ø9814Ø-6 and transgenic soybeans containing event DP-356Ø43-5: Laying hen performance and egg quality measures

Abstract: The objective of this study was to compare the nutritional performance of laying hens fed maize grain from event DP-Ø9814Ø-6 (98140; gat4621 and zm-hra genes) and processed soybean meal from soybeans containing event DP-356Ø43-5 (356043; gat4601 and gm-hra genes), individually or in combination, with the performance of hens fed diets containing nontransgenic maize and soybean meal. Healthy pullets (n = 216) placed in cages (3 hens/cage) were randomly assigned to 9 dietary treatments (8 cages/treatment): nontra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
18
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 10 publications
4
18
0
Order By: Relevance
“…These results demonstrated no differences in nutritional performance of laying hens fed the transgenic corn diets when compared with laying hens fed the non-transgenic control diets; statistical analysis of the data in this study resulted in rejection of all hypotheses of different performance and egg quality. In agreement with these findings, previous studies with laying hens have shown that laying hen performance and egg quality is not affected by corn conferring pesticide resistance (Jacobs et al, 2008;Halle and Flachowsky, 2014) or herbicide tolerance traits (McNaughton et al, 2011). Transgenic feed have minimal effect on the small intestinal histology, which has been demonstrated in several studies.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…These results demonstrated no differences in nutritional performance of laying hens fed the transgenic corn diets when compared with laying hens fed the non-transgenic control diets; statistical analysis of the data in this study resulted in rejection of all hypotheses of different performance and egg quality. In agreement with these findings, previous studies with laying hens have shown that laying hen performance and egg quality is not affected by corn conferring pesticide resistance (Jacobs et al, 2008;Halle and Flachowsky, 2014) or herbicide tolerance traits (McNaughton et al, 2011). Transgenic feed have minimal effect on the small intestinal histology, which has been demonstrated in several studies.…”
Section: Discussionsupporting
confidence: 85%
“…Carcass yield or any individual parts yield was similar between the transgenic and control diets in the present study. This result is consistent with the observation that carcass yield of broilers was not affected by the BT corn diet (Brake and Vlachos, 1998;Aeschbacher et al, 2005) and by corn containing the glyphosate acetyltransferase gene (Taylor et al, 2005;McNaughton et al, 2011). …”
supporting
confidence: 91%
See 2 more Smart Citations
“…The Bt gene is the most effective and widely used insect toxin gene. Various studies have been conducted to evaluate the effect of Bt crops on animals (Michelle et al, 2007;Guertler et al, 2010;Grønsberg et al, 2011;McNaughton et al, 2011). Bioassays to determine insect resistance have revealed that the chitinaseBmkIT combination has lethal or growth-inhibiting effects on diamondback moth (Plutella maculipenis) larvae (Wang et al, 2005) and fall webworm (Hyphantria cunea) larvae (Yang et al, 2008), which confirms that the chitinaseBmkIT combination could be used as a new pest-resistant gene source and might be a complementary alien gene source to the Bt toxin gene.…”
Section: Introductionmentioning
confidence: 99%